Flux self-increasing ZnIn2S4 / PVDF photocatalytic composite membrane as well as preparation method and anti-pollution application of flux self-increasing ZnIn2S4 / PVDF photocatalytic composite membrane

By uniformly dispersing the ZnIn2S4 nanophotocatalyst in the PVDF film, forming the ZnIn2S4/PVDF photocatalytic composite film, the problems of film pollution and flux reduction are solved, and efficient degradation of organic pollutants in water bodies and membrane self-cleaning functions are achieved.

CN119656889APending Publication Date: 2025-03-21SHANGHAI NORMAL UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411856781.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

During the application process, existing membrane separation technology is susceptible to problems such as membrane pollution, reduced flux and poor photocatalyst stability, making it difficult to effectively remove organic pollutants in water bodies.

Method used

The ZnIn2S4 nanophotocatalyst was synthesized by hydrothermal method, and it was evenly dispersed into the PVDF film matrix by phase conversion method to form a ZnIn2S4/PVDF photocatalytic composite film, which improved the hydrophilicity, antifouling performance and photocatalytic activity of the film.

Benefits of technology

It realizes self-improvement and stability of water flux, significantly improves the degradation efficiency of organic pollutants in water, extends the service life of the membrane, and has dynamic self-cleaning function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656889A_ABST
    Figure CN119656889A_ABST
Patent Text Reader

Abstract

The invention discloses a flux self-lifting ZnIn2S4 / PVDF (polyvinylidene fluoride) photocatalytic composite membrane as well as a preparation method and anti-pollution application thereof, and the method comprises the following steps: synthesizing a ZnIn2S4 photocatalyst with a nano spherical structure by adopting a hydrothermal method, dispersing the ZnIn2S4 photocatalyst in a PVDF membrane casting solution, and preparing the composite membrane by adopting a phase inversion method. The membrane has an asymmetric spongy communicated pore channel structure, and ZnIn2S4 is uniformly distributed in a membrane matrix, so that the hydrophilicity, antifouling property and photocatalytic degradation capacity of the membrane are remarkably improved. The photocatalytic membrane shows excellent separation and degradation performance on humic acid in a water body under the condition of visible light, the retention rate exceeds 90%, meanwhile, the flux is continuously increased, the flux recovery rate exceeds 100%, and flux reduction caused by pollution and blockage of a traditional photocatalytic composite membrane is effectively avoided. The preparation method is simple to operate and controllable in condition, and the composite membrane has efficient antifouling and self-cleaning performance and is suitable for the fields of drinking water purification, industrial wastewater treatment and other water pollution treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of semiconductor photocatalysis technology and membrane separation technology, and specifically relates to a method for preparing a flux self-enhancing ZnIn2S4 / PVDF photocatalytic composite membrane and its high-efficiency anti-pollution application in water pollutant treatment. Background Art

[0002] As an efficient and energy-saving separation process, membrane separation has been widely used in pollutant removal. Through the principle of physical screening, it can effectively remove suspended particles, bacteria and some organic pollutants in water. However, membranes are easily affected by accumulated pollutants during long-term use, resulting in pore blockage, which leads to decreased flux, reduced separation efficiency, reduced service life and increased maintenance costs. Therefore, membrane pollution has become one of the main bottlenecks restricting the further promotion and application of membrane separation technology.

[0003] In order to deal with the problem of membrane fouling, researchers have proposed a variety of methods such as membrane surface modification and photocatalytic nanoparticle doping. Among them, surface modification technology reduces the adhesion of pollutants to reduce membrane fouling by changing the hydrophilicity, charge and roughness of the membrane surface. However, pollutants still cannot be effectively removed, and the problem of membrane fouling exists during long-term use. The use of photocatalytic nanoparticle doping can not only improve the surface performance of the membrane, but also effectively degrade and mineralize pollutants to prevent membrane fouling. However, in the current research on photocatalytic coupled membrane separation systems, photocatalysts still have problems such as insufficient light response range, low photodegradation efficiency, and the agglomeration behavior of the particles themselves leading to blockage of membrane pores. Therefore, it is of great significance to select suitable photocatalysts to construct a photocatalytic membrane separation system with high efficiency anti-fouling performance. Summary of the invention

[0004] In order to overcome the limitations of existing membrane separation technology that is susceptible to membrane pollution, flux decline, and poor stability of photocatalysts during application, the present invention provides a ZnIn2S4 / PVDF photocatalytic composite membrane with a flux self-boosting effect, a preparation method thereof, and anti-fouling applications. The composite membrane is prepared by uniformly dispersing the ZnIn2S4 nanophotocatalyst into a PVDF matrix, and the hydrophilicity, antifouling performance, and photocatalytic activity of the membrane are significantly improved by finely controlling the structure, loading amount, and distribution of the photocatalyst. The preparation method proposed in the present invention synthesizes the ZnIn2S4 photocatalyst by a hydrothermal method, and introduces it into the PVDF casting solution by a phase inversion method, combining the advantages of semiconductor photocatalysis and membrane separation technology, not only effectively improving the membrane surface performance, but also achieving efficient degradation of organic pollutants (such as humic acid) in the water body, so that the flux is self-boosted and maintains stability and self-cleaning ability. The present invention can be widely used in industrial wastewater treatment, drinking water purification, and other water pollution control scenarios.

[0005] According to a first aspect of the present invention, a ZnIn2S4 / PVDF photocatalytic composite membrane having a flux self-boosting effect is provided, comprising:

[0006] PVDF membrane substrate;

[0007] ZnIn2S4 photocatalyst uniformly dispersed in the pores of the PVDF membrane matrix;

[0008] Among them, the ZnIn2S4 photocatalyst has a nano-spherical structure. The ZnIn2S4 photocatalyst has the ability to photocatalytically degrade pollutants under visible light irradiation, can dynamically increase water flux during use, and effectively improve the hydrophilicity and anti-fouling properties of the PVDF membrane.

[0009] In some technical solutions, the composite membrane is an ultrafiltration membrane having an asymmetric sponge-like interconnected pore structure.

[0010] In some technical solutions, the amount of ZnIn2S4 added to the casting solution is 1.0-4.0wt%;

[0011] The amount of PVDF added to the casting solution is 12-15wt%;

[0012] The amount of the pore-forming agent PVP added to the casting solution is 0-3.0 wt %.

[0013] In some technical solutions, the composite membrane has the following properties:

[0014] Under visible light irradiation conditions, the water flux continued to increase;

[0015] After photocatalysis, the membrane flux recovery rate reaches or exceeds the initial flux.

[0016] According to a second aspect of the present invention, there is further provided a method for preparing a ZnIn2S4 / PVDF photocatalytic composite membrane having a flux self-boosting effect, comprising the following steps:

[0017] Preparation of photocatalyst: Zn(CH3COO)2·2H2O, C2H5NS and InCl3·4H2O were dissolved in deionized water and subjected to hydrothermal reaction to obtain ZnIn2S4 nano-photocatalyst;

[0018] Preparation of casting solution: Disperse ZnIn2S4 nano-photocatalyst uniformly in an organic solvent, add PVDF and pore-forming agent PVP, stir evenly and let stand to degas, and obtain casting solution;

[0019] Forming of the composite membrane: The casting solution is coated on a substrate by a phase inversion method, formed and cured to obtain a ZnIn2S4 / PVDF photocatalytic composite membrane.

[0020] As a preferred embodiment, the steps of preparing the photocatalyst include:

[0021] Zn(CH3COO)2·2H2O, C2H5NS, and InCl3·4H2O were dissolved in deionized water in a molar ratio of 1:4:2;

[0022] React at 180-200°C for 12-18 hours;

[0023] After cooling, the product is washed, dried and ground to obtain a ZnIn2S4 nano-photocatalyst.

[0024] As a preferred embodiment, the steps of preparing the casting solution include:

[0025] The ZnIn2S4 nano-photocatalyst is uniformly dispersed in an organic solvent, wherein the organic solvent is one or more of DMF, DMAc or DMSO;

[0026] Add PVDF powder material and pore-forming agent PVP to the dispersion, and heat the mixture to 60-70°C and stir evenly;

[0027] The mixture was allowed to stand for 3-5 hours to degas and obtain a casting solution.

[0028] As a preferred embodiment, the step of forming the composite film comprises:

[0029] Use an automatic coating machine to coat the casting solution on the substrate with a coating thickness of 0.2-0.3 μm;

[0030] The coated substrate is immersed in a coagulation bath at room temperature or 25°C to allow the film to solidify and then fall off;

[0031] The detached membrane was soaked in deionized water to remove the residual solvent.

[0032] According to the third aspect of the present invention, there is further provided an application of a ZnIn2S4 / PVDF photocatalytic composite membrane having a flux self-boosting effect in the treatment of water pollutants, for:

[0033] Degrade humic acid or other organic pollutants in water under visible light conditions, and improve the self-cleaning and anti-pollution properties of the composite membrane.

[0034] As a preferred solution, the ZnIn2S4 / PVDF photocatalytic composite membrane is suitable for the following fields:

[0035] Anti-fouling membrane separation operations in industrial wastewater treatment, drinking water purification and environmental protection.

[0036] The present invention adopts the above technical solution to have at least the following beneficial effects:

[0037] 1. The ZnIn2S4 nanoparticles of the present invention are evenly distributed in the pores of the PVDF matrix, which significantly improves the hydrophilicity of the membrane surface. In particular, in the process of pollutant removal, the water flux can be gradually improved, and the attachment of pollutants on the membrane surface can be effectively reduced, thereby improving the membrane's separation efficiency for pollutants, reducing the risk of membrane contamination, and thus extending the service life of the membrane.

[0038] 2. The nanostructure of ZnIn2S4, a ternary sulfide semiconductor material with a layered structure and a wide light response range, provides a large specific surface area and excellent photocatalytic activity. Under visible light conditions, ZnIn2S4 can efficiently degrade organic pollutants in water such as humic acid, showing excellent photocatalytic degradation performance.

[0039] 3. The ZnIn2S4 / PVDF composite membrane prepared by the present invention shows a trend of continuous increase in flux during the degradation of pollutants, avoiding the flux decline problem caused by pollution of traditional membranes. At the same time, the active species generated by the photocatalyst under the action of visible light can decompose organic matter attached to the membrane surface, realize the dynamic self-cleaning function of the membrane surface, and its flux recovery rate can reach or exceed 100%.

[0040] 4. The present invention adopts a hydrothermal method to synthesize the photocatalyst and prepares the composite membrane by a phase conversion method, which has a simple process and controllable conditions. By adjusting the loading amount of ZnIn2S4 and the membrane structure parameters, it can meet the treatment requirements of different pollutants and realize personalized design.

[0041] 5. The ZnIn2S4 / PVDF photocatalytic composite membrane of the present invention has significant advantages in treating organic pollutants such as humic acid, and is also suitable for separating and purifying other pollutants in water. Its excellent antifouling and self-cleaning properties provide a new solution for membrane separation technology in the fields of drinking water purification, industrial wastewater treatment and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 X-ray diffraction (XRD) patterns of the film samples prepared in Examples 1 to 4 and Comparative Examples 1 to 3;

[0043] Figure 2 The UV-visible diffuse reflectance (UV-vis DRS) spectra of the film samples prepared in Examples 1 to 4 and Comparative Examples 1 to 3;

[0044] Figure 3 Scanning electron microscope (SEM) images of the film samples prepared in Examples 1 to 4;

[0045] Figure 4 Scanning electron microscope (SEM) images of the film samples prepared in Example 1 and Comparative Examples 1 to 3;

[0046] Figure 5 The water contact angle (CA) test diagram of the film samples prepared in Examples 1 to 4;

[0047] Figure 6 The water contact angle (CA) test diagram of the film samples prepared in Example 1 and Comparative Examples 1 to 3;

[0048] Figure 7 This is a pure water flux test diagram of the membrane samples prepared in Examples 1 to 4;

[0049] Figure 8 The pure water flux test diagram of the membrane samples prepared in Example 1 and Comparative Examples 1 to 3;

[0050] Fig. 9 This is a test graph of the retention rate of the membrane samples prepared in Examples 1 to 4 for humic acid solution (HA);

[0051] Fig.10 Test graph of the retention rate of humic acid solution (HA) of the membrane samples prepared in Example 1 and Comparative Examples 1 to 3;

[0052] Fig.11 The anti-fouling performance test diagram of the membrane samples prepared in Examples 1 to 4;

[0053] Fig.12 The anti-fouling performance test diagram of the membrane samples prepared in Example 1 and Comparative Examples 1 to 3;

[0054] Fig.13 The water contact angle test diagram of the membrane samples prepared in Examples 1 to 4 after being treated with humic acid;

[0055] Fig.14 The water contact angle test diagram of the film samples prepared in Example 1 and Comparative Examples 1 to 3 after being treated with humic acid;

[0056] Fig.15 The self-cleaning performance test diagram of the membrane samples prepared in Example 1 and Comparative Examples 1 to 3;

[0057] Fig.16 The graph is a cyclic stability test graph of the membrane samples prepared in Example 1 and Comparative Examples 1 to 3. DETAILED DESCRIPTION

[0058] The present invention is further fully described below in conjunction with specific examples. The following examples do not limit the protection scope of the present invention.

[0059] Example 1

[0060] Step (1): Preparation of ZnIn2S4 photocatalyst. Dissolve Zn(CH3COO)2·2H2O (2mmol), C2H5NS (8mmol) and InCl3·4H2O (4mmol) in 60mL of deionized water, sonicate until completely dissolved, transfer the mixed solution to a hydrothermal reactor, react at 180°C for 16h, cool to room temperature, wash with deionized water and ethanol three times respectively, dry and grind to obtain ZnIn2S4 nanophotocatalyst.

[0061] Step (2): Preparation of ZnIn2S4 / PVDF composite membrane. Take 0.9g of the prepared ZnIn2S4 photocatalyst (3.0wt%), ultrasonically disperse it in 24.6g (82wt%) DMF, transfer it to a three-necked flask and add 0.9g (3.0wt%) PVP and 3.6g (12wt%) PVDF powder material, heat and stir at 60°C to completely dissolve the powder material to obtain a casting solution. Place it in a vacuum drying oven for degassing for 4h, then pour the casting solution onto a glass plate, and use an automatic coating machine with a scraper set to a height of 0.25μm to scrape it into a film. Immerse the glass plate with the film in a room temperature coagulation bath to solidify and fall off the film. Cut the film and collect it in deionized water to obtain a ZnIn2S4 / PVDF photocatalytic membrane, recorded as ZIS / PVDF-3.

[0062] Example 2

[0063] The preparation method of this embodiment is consistent with that of Example 1, with the only difference being that in step (2), the amount of ZnIn2S4 photocatalyst added is 0.3 g (i.e. 1.0 wt%), the amount of solvent DMF used is 25.2 g (i.e. 84 wt%), and the resulting ZnIn2S4 / PVDF photocatalytic film is denoted as ZIS / PVDF-1.

[0064] Example 3

[0065] The preparation method of this embodiment is consistent with that of Example 1, with the only difference being that in step (2), the amount of ZnIn2S4 photocatalyst added is 0.6 g (i.e. 2.0 wt%), the amount of solvent DMF used is 24.9 g (i.e. 83 wt%), and the resulting ZnIn2S4 / PVDF photocatalytic film is denoted as ZIS / PVDF-2.

[0066] Example 4

[0067] The preparation method of this embodiment is consistent with that of Example 1, with the only difference being that in step (2), the amount of ZnIn2S4 photocatalyst added is 1.2 g (i.e. 4.0 wt%), the amount of solvent DMF used is 24.3 g (i.e. 81 wt%), and the resulting ZnIn2S4 / PVDF photocatalytic film is denoted as ZIS / PVDF-4.

[0068] Comparative Example 1

[0069] The preparation method of this comparative example is consistent with that of Example 1, except that in step (2), no ZnIn2S4 photocatalyst is added, the amount of solvent DMF used is 25.5 g (ie, 85 wt%), and a PVDF membrane is obtained.

[0070] Comparative Example 2

[0071] The preparation method of this comparative example is basically the same as that of Example 1, except that, in step (1), In2S3 photocatalyst is prepared. C2H5NS (8.0mmol) and InCl3·4H2O (5.33mmol) are dissolved in 60mL of deionized water, ultrasonicated until completely dissolved, and the mixed solution is transferred to a hydrothermal kettle, reacted at 180°C for 16h, cooled to room temperature, washed three times with deionized water and ethanol respectively, dried and ground to obtain In2S3 nanophotocatalyst. In step (2), ZnIn2S4 is replaced with In2S3 to prepare a composite film, and the obtained In2S3 / PVDF photocatalytic film is recorded as IS / PVDF-3.

[0072] Comparative Example 3

[0073] The preparation method of this comparative example is basically the same as that of Example 1, except that in step (1), a ZnS photocatalyst is prepared. Zn(CH3COO)2·2H2O (8.0mmol) and C2H5NS (8.0mmol) are dissolved in 60mL of deionized water, ultrasonicated until completely dissolved, and the mixed solution is transferred to a hydrothermal kettle, reacted at a high temperature of 180°C for 16h, cooled to room temperature, washed three times with deionized water and ethanol respectively, dried and ground to obtain a ZnS nanophotocatalyst. In step (2), ZnIn2S4 is replaced by ZnS to prepare a composite membrane, and the resulting ZnS / PVDF photocatalytic membrane is recorded as ZS / PVDF-3.

[0074] Test Example 1: Characterization of ZnIn2S4 / PVDF Photocatalytic Film

[0075] Characterization method: The structure was analyzed by X-ray diffractometer (XRD, Rigaku D / Max-RB); the light absorption performance was analyzed by ultraviolet visible diffuse reflectance (UV-vis DRS, UV-2450); the morphology was analyzed by scanning electron microscopy (SEM, HITACHI S-4800); and the water contact angle (CA) was tested by contact angle analyzer (JC2000D1).

[0076] Figure 1The XRD spectra of different membrane samples are shown. Different ZIS / PVDF composite membranes all show the characteristic diffraction peaks of ZnIn2S4, and the peak positions are consistent. With the increase of ZnIn2S4 loading, the characteristic peak intensity of ZnIn2S4 gradually increases, indicating that ZIS / PVDF composite membranes with different proportions have been successfully synthesized. ZS / PVDF-3 and IS / PVDF-3 show the characteristic diffraction peaks of ZnS and In2S3, respectively, proving that different membrane samples have successfully loaded photocatalysts.

[0077] Figure 2 The UV-DRS absorption spectra of different membrane samples are shown. The ZIS / PVDF-3 composite membrane prepared in Example 1 has a wider light absorption range than that of Examples 2-3, and the visible light absorption capacity is significantly enhanced. Therefore, the improvement of light utilization is conducive to promoting photocatalytic degradation of pollutants. In addition, the absorption wavelength range of Example 1 is similar to that of Example 4, indicating that the best light absorption capacity can be obtained when the ZnIn2S4 loading is 3.0wt%. Considering the economic benefits, the photocatalyst loading ratio in Example 1 is determined to be the optimal ratio.

[0078] Figure 3-4 The surface morphology and cross-sectional structure of different membrane samples are shown. The ZIS / PVDF composite membranes all show a sponge-like porous structure, and nano-spherical ZnIn2S4 particles can be observed distributed inside the PVDF membrane pores, indicating that ZnIn2S4 is uniformly dispersed in the PVDF matrix and forms a stable composite structure, which is conducive to the penetration of water molecules or pollutants and the progress of photocatalytic reactions. The surface of the pure PVDF membrane is dense and the cross-sectional structure is asymmetric. In Example 4, the excess ZnIn2S4 in ZIS / PVDF-4 leads to a larger membrane pore size, which is not conducive to the retention of pollutants.

[0079] Figure 5-6 Water contact angle data for different membrane samples are shown. Figure 5 It shows that the increase in ZnIn2S4 loading is beneficial to improving the hydrophilicity of the membrane surface, thereby increasing water flux and reducing pollutant attachment, promoting separation efficiency and antifouling performance. Figure 6 It shows that the contact angle of the PVDF membrane of Comparative Example 1 is greater than 90 o The introduction of photocatalyst can effectively reduce the water contact angle and improve the hydrophilicity of the membrane surface. Different catalysts have similar effects on improving hydrophilicity, all of which show a hydrophilic membrane with a contact angle of less than 90o. Among them, IS / PVDF-3du in comparative example 2 shows the best hydrophilicity. Therefore. Loading the catalyst is beneficial to improving the anti-pollution performance of the PVDF membrane.

[0080] Test Example 2: ZnIn2S4 / PVDF photocatalytic film performance test

[0081] The pure water flux of the membrane samples described in each embodiment of the present invention is tested by circulating cross-flow method. The membrane samples are fixed in the membrane filtration unit, and the effective filtration area is 28.3cm 2 First, the membrane sample was pre-pressed with deionized water at a pressure of 1.0 bar for 30 minutes to stabilize the water flux. Then the membrane port pressure was set to 0.5 bar. The weight of deionized water passing through the membrane sample every 3 minutes was recorded in real time by an electronic balance. The average water flux of the membrane sample was calculated based on the recorded data. The calculation formula is:

[0082] J=V / (A·t·P)

[0083] Where J is the water flux (L·m -2 ·h -1 bar), V is the volume of the permeate liquid (L), A is the effective area of ​​the membrane filtration (m 2 ), t is the filtration time (h), and P is the transmembrane pressure (bar).

[0084] The retention rate test experiment of the membrane samples described in each embodiment of the present invention is tested by circulating cross-flow method. The membrane sample is fixed in the membrane filtration unit, and the effective filtration area is 28.3cm 2 First, the membrane sample was pre-pressed with deionized water at a pressure of 1.0 bar for 30 minutes to stabilize the water flux, and then the deionized water was replaced with a humic acid solution (solution A, 10 mg / L), the membrane port pressure was set to 0.5 bar, and the filtered solution (solution B) passed by the membrane sample was collected. The absorbance of solutions A and B was measured at 245 nm using a UV-visible spectrophotometer, and the humic acid concentration and pollutant retention rate were calculated according to the Lambert-Beer law. The calculation formula is:

[0085] R=1-C / C0

[0086] Where R is the retention rate (%), C is the concentration of the permeate after filtration, and C0 is the concentration of the pollutant mother liquor in the feed tank.

[0087] The antifouling and self-cleaning performance test experimental process of the membrane samples described in each embodiment of the present invention is as follows: (1) The experimental process is consistent with the above-mentioned pure water flux test, wherein the filtration time is 30 minutes, the volume of the permeate measured liquid is recorded every 3 minutes, and the pure water flux (J) is calculated. w ); (2) replace deionized water with humic acid solution, set the membrane port pressure to 0.5 bar and filter for 30 minutes to make the membrane contaminated with humic acid, then rinse with deionized water for 5 minutes to remove the contaminants attached to the membrane surface; (3) replace the humic acid solution with deionized water and filter at 0.5 bar for 30 minutes, record the volume of liquid collected in the permeation measurement every 3 minutes and calculate the pure water flux after membrane contamination (J f); (4) Stop filtering, during which the membrane is placed under visible light irradiation. After 120 min of irradiation, the light source is turned off, and deionized water is used for filtration at a pressure of 0.5 bar for 30 min. The volume of the collected liquid in the permeation measurement is recorded every 3 min and the pure water flux after self-cleaning under light irradiation is calculated (J c The above steps (2) to (4) were repeated three times to test the stability of the membrane material.

[0088] Figure 7-8 Pure water fluxes of different membrane samples are shown. Figure 7 It shows that the increase of ZnIn2S4 loading is conducive to the improvement of membrane water flux. With the increase of loading, the water flux shows an upward trend. Figure 5 The results of the medium contact angles are consistent, indicating that the loading of ZnIn2S4 is conducive to improving the hydrophilicity of the composite membrane and increasing the water flux. However, excessive loading (ZIS / PVDF-4 in Example 4) may cause catalyst agglomeration and block the membrane pores, resulting in the inability to further increase the water flux. Figure 8 It shows that the loading of ZnIn2S4 effectively improves the water flux of the membrane. When the loading ratio reaches 2wt% (Example 3), the water flux improvement effect is significantly enhanced. When the loading ratio is 3wt% (Example 1), the effect is optimal. Compared with the pure PVDF membrane of Comparative Example 1, the water flux is increased by 170%. In addition to the improvement of hydrophilicity, it can also be attributed to the improvement of the membrane pore structure by ZnIn2S4. Figure 3 The sponge-like pores shown in the graph greatly improve the ability of the composite membrane to filter water. In comparative examples 2-3, the loading of ZnS and In2S3 has little effect on improving the water flux of the PVDF membrane. Figure 6 The hydrophilicity of the corresponding composite membrane is improved, but combined with Figure 4 It can be inferred that the loading of ZnS and In2S3 has little effect on the modification of membrane pores.

[0089] Figure 9-10 The retention rates of HA by different membrane samples under visible light and without light irradiation are shown. Fig. 9 Compared with pure PVDF membrane, the photocatalyst loaded in Example 1 and Comparative Examples 2-3 can effectively improve the retention rate of HA by PVDF membrane. The retention rate can be maintained above 90% under dark conditions, which is attributed to the fact that the loaded catalyst can effectively improve the hydrophilicity of the membrane and reduce the adhesion of pollutants. The comparison of the retention rate under visible light and no light conditions shows that the photocatalyst effectively plays a role in the degradation and removal of pollutants. Fig.10 The effects of different ZnIn2S4 loading amounts on the membrane retention performance were shown, and a high retention rate was shown under visible light, reflecting the efficient degradation ability of ZnIn2S4 for HA.

[0090] Figure 11-12The antifouling performance of different membrane samples is shown. Fig.11 The ZIS / PVDF membrane showed high antifouling performance and achieved continuous improvement in normalized flux. At the same time, with the increase of ZnIn2S4 loading, its antifouling performance increased. When the loading was less than 2wt%, the flux could be restored to the initial flux level in 5h, and the flux enhancement effect was not obvious. When the loading was 3wt%, it had a significant flux enhancement effect, and the flux increased by nearly 70% after 5h. The flux enhancement effect of ZIS / PVDF-4 was relatively reduced, which can be attributed to the fact that the excessively loaded catalyst may cause partial blockage of the membrane pores. Fig.12 It shows that other membrane samples all show a downward trend in normalized flux, indicating that the high antifouling performance of ZIS / PVDF membrane and the continuous increase in flux can be attributed to the visible light degradation of HA by ZnIn2S4 in the membrane pores, preventing the membrane pores from being contaminated and blocked by HA. The following will provide a detailed analysis.

[0091] Figure 13-14 The contact angles of different membrane samples before and after HA treatment under visible light and without light source are shown. Compared with no degradation effect on HA under no light source irradiation conditions, ZnIn2S4 in the ZIS / PVDF membrane photocatalytically degrades HA under visible light for 5 hours, and the composite membrane shows a significant improvement in hydrophilicity. This can be attributed to the production of degradation products that enhance the hydrophilicity of the membrane surface during the degradation of HA by ZIS / PVDF, thus achieving dynamic modification of membrane performance. However, pure PVDF membranes without catalyst loading, PVDF membranes loaded with ZnS (no visible light response), and PVDF membranes loaded with In2S3 (weak HA degradation effect under visible light) all have no such effect. Therefore, ZIS / PVD membranes can achieve Fig.11 The high antifouling performance and continuous improvement of membrane flux are shown.

[0092] Fig.15 The self-cleaning performance test results of the membrane sample of Example 1 are shown. The figure shows that the membrane samples in Comparative Examples 1 to 3 all exhibit poor self-cleaning ability. After three self-cleaning cycle experiments, the flux decreased by more than 40%. The ZIS / PVDF-3 membrane exhibits excellent self-cleaning performance. In the first cycle, the flux recovered after rinsing with deionized water compared with the HA solution pollution process, indicating that it has good hydrophilicity, and the membrane surface is not easily attached by pollutants. Simple water rinsing can restore the flux by 20%. After illumination, the flux not only fully recovered but also exceeded the initial level, reaching 140%, which is attributed to the efficient degradation and removal of HA by ZnIn2S4, and the degradation products that enhance the hydrophilicity of the membrane surface during the degradation process. And in the second and third cycles, the efficient self-cleaning ability is still maintained, and the flux recovery rate exceeds 100%, which exceeds the level of existing research on the modification of PVDF membranes to enhance the self-cleaning performance.

[0093] Fig.16The test results of the cyclic stability performance of the membrane sample of Example 1 are shown. The membrane samples in Comparative Examples 1 to 3 all showed a decrease in flux after the cycle, indicating that the pores were blocked due to pollution. The ZIS / PVDF-3 of Example 1 showed a continuous increase in flux in the first two cycles, and reached a stable high flux level after the flux was increased in the third cycle. This can be attributed to the excellent hydrophilicity of the ZIS / PVDF membrane, which reduces the adhesion of pollutants on the membrane surface, and its efficient degradation ability for HA, which makes the membrane have efficient self-cleaning ability. At the same time, the improvement of the hydrophilicity of the membrane in the dynamic process shown in the anti-fouling performance test enables the ZIS / PVDF-3 membrane to have a continuous increase in flux when treating HA solutions.

[0094] Previous studies have shown that when the antifouling performance is improved by surface modification or nanoparticle doping, it is impossible to effectively and completely degrade and remove pollutants accumulated on the membrane, which inevitably causes clogging problems and leads to a decrease in flux. The ZnIn2S4 / PVDF photocatalytic composite ultrafiltration membrane designed by the present invention not only modifies the membrane surface performance and pore structure and imparts photocatalytic degradation ability, but also achieves further improvement of the hydrophilicity of the membrane surface during the visible light catalytic reaction, avoids membrane pollution, exhibits efficient antifouling performance, and achieves continuous improvement of flux in the process of treating HA, providing a new strategy for solving the membrane pollution problem and a feasible solution for treating water pollution by membrane separation technology.

[0095] It should be noted that the above-described implementation method is a preferred embodiment of the present invention, but the present invention is not limited thereto. A person skilled in the art may make changes and improvements based on the technical solution described in the present invention, and the changes and improvements in the scope of protection of the claims of the present invention should not be limited to the contents listed in the specific embodiments.

Claims

1. A ZnIn2S4 / PVDF photocatalytic composite membrane with flux self-enhancing effect, characterized in that: include: PVDF membrane substrate; ZnIn2S4 photocatalyst uniformly dispersed in the pores of the PVDF membrane matrix; Among them, the ZnIn2S4 photocatalyst has a nano-spherical structure. The ZnIn2S4 photocatalyst has the ability to photocatalytically degrade pollutants under visible light irradiation, can dynamically increase water flux during use, and effectively improve the hydrophilicity and anti-fouling properties of the PVDF membrane.

2. The ZnIn2S4 / PVDF photocatalytic composite membrane according to claim 1, characterized in that: The composite membrane is an ultrafiltration membrane having an asymmetric sponge-like interconnected pore structure.

3. The ZnIn2S4 / PVDF photocatalytic composite membrane according to claim 1, characterized in that: The amount of ZnIn2S4 added to the casting solution is 1.0-4.0wt%; The amount of PVDF added to the casting solution is 12-15wt%; The amount of the pore-forming agent PVP added to the casting solution is 0-3.0 wt %.

4. The ZnIn2S4 / PVDF photocatalytic composite membrane according to claim 1, characterized in that: The composite film has the following properties: Under visible light irradiation conditions, the water flux continued to increase; After photocatalysis, the membrane flux recovery rate reaches or exceeds the initial flux.

5. A method for preparing a ZnIn2S4 / PVDF photocatalytic composite membrane with a flux self-enhancing effect, characterized in that: The following steps are involved: Preparation of photocatalyst: Zn(CH3COO)2·2H2O, C2H5NS and InCl3·4H2O were dissolved in deionized water and subjected to hydrothermal reaction to obtain ZnIn2S4 nano-photocatalyst; Preparation of casting solution: Disperse ZnIn2S4 nano-photocatalyst uniformly in an organic solvent, add PVDF and pore-forming agent PVP, stir evenly and let stand to degas, and obtain casting solution; Forming of the composite membrane: The casting solution is coated on a substrate by a phase inversion method, formed and cured to obtain a ZnIn2S4 / PVDF photocatalytic composite membrane.

6. The preparation method according to claim 5, characterized in that: The preparation steps of the photocatalyst include: Zn(CH3COO)2·2H2O, C2H5NS, and InCl3·4H2O were dissolved in deionized water in a molar ratio of 1:4:2; React at 180-200°C for 12-18 hours; After cooling, the product is washed, dried and ground to obtain a ZnIn2S4 nano-photocatalyst.

7. The preparation method according to claim 5, characterized in that: The preparation steps of the casting solution include: The ZnIn2S4 nano-photocatalyst is uniformly dispersed in an organic solvent, wherein the organic solvent is one or more of DMF, DMAc or DMSO; Add PVDF powder material and pore-forming agent PVP to the dispersion, and heat the mixture to 60-70°C and stir evenly; The mixture was allowed to stand for 3-5 hours to degas and obtain a casting solution.

8. The preparation method according to claim 5, characterized in that: The forming step of the composite film comprises: Use an automatic coating machine to coat the casting solution on the substrate with a coating thickness of 0.2-0.3 μm; The coated substrate is immersed in a coagulation bath at room temperature or 25°C to allow the film to solidify and then fall off; The detached membrane was soaked in deionized water to remove the residual solvent.

9. Application of a ZnIn2S4 / PVDF photocatalytic composite membrane with flux self-enhancing effect in water pollutant treatment, characterized in that: The ZnIn2S4 / PVDF photocatalytic composite film is prepared according to any one of claims 1 to 4, or the preparation method according to any one of claims 5 to 8; it is mainly used for: Degrade humic acid or other organic pollutants in water under visible light conditions, and improve the flux recovery rate and anti-pollution performance of the composite membrane.

10. The use according to claim 9, characterized in that: The ZnIn2S4 / PVDF photocatalytic composite membrane is suitable for the following fields: Anti-fouling membrane separation operations in industrial wastewater treatment, drinking water purification and environmental protection.

Citation Information

Patent Citations

  • PVDF (Polyvinylidene Fluoride) ultrafiltration membrane compounded with Ag-coated BiOBr photocatalytic material as well as preparation method and application of PVDF ultrafiltration membrane

    CN113546523A

  • Surface composite photocatalytic membrane, preparation method thereof and application of surface composite photocatalytic membrane in water treatment

    CN116173986A

  • Preparation method and application of ZnIn2S4 / PVDF composite photocatalytic membrane

    CN117181313A